Humanism according to Raja Haji Yahya, a Malay Muslim poet from Perak in the early 20th century - Khairul Nizam Bin Zainal Badri (Al-Hikmah: Jurnal Dakwah dan Ilmu Komunikasi, 2021)
Humanism became a central or important point in civilization because it was often associated with the intellectual movement. This study sought to look at the idea of a Malay literary figures of the 19th and early 20th century, a native of Perak, Raja Haji Yahya about aspects of humanism in his literary work. Qualitative methods with a literature approach were used to achieve the objectives of the study. The results of the study found that Raja Haji Yahya has used poetry as a medium to pour out the essence of humanity in the form of cynical metaphors. This is because at that time, the ruling power of the original inhabitants was taken over by the British colonialists. Following the British entry into the state of Perak, the landscape of governance and community life gradually underwent changes. According to Raja Haji Yahya, the society was divided, with one side being a supporter of the colonialists and the other being an opponent.